2001
DOI: 10.1097/00006534-200109010-00011
|View full text |Cite
|
Sign up to set email alerts
|

An in Vivo Comparison of Topical Agents on Wound Repair

Abstract: Selection of the ideal antiseptic or antimicrobial treatment for contaminated wounds remains a controversial decision. Clinical decisions are often made on the basis of in vitro studies and personal preference. Although topical solutions are widely used, their comparative in vivo effects on wound healing are largely unreported.A porcine wound model was used to compare five commonly used topical agents-5% mafenide acetate (Sulfamylon solution), 10% povidone with 1% free iodine (Betadine), 0.25% sodium hypochlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 22 publications
2
42
0
2
Order By: Relevance
“…This paradigm of tissue repair has been used to demonstrate the efficacy of various wound healing treatments, because this animal model most closely mimics human wound healing. 36,37 For example, porcine and human skin share similar epidermal and dermal-epidermal thickness ratios, mosaic hair growth, and have similar hair and blood vessel distribution. To approach the problem of defective wound healing posed by diseases such as diabetes, we also sought to determine whether CRT would enhance repair in steroid-treated pigs, as a model of impaired wound healing.…”
mentioning
confidence: 99%
“…This paradigm of tissue repair has been used to demonstrate the efficacy of various wound healing treatments, because this animal model most closely mimics human wound healing. 36,37 For example, porcine and human skin share similar epidermal and dermal-epidermal thickness ratios, mosaic hair growth, and have similar hair and blood vessel distribution. To approach the problem of defective wound healing posed by diseases such as diabetes, we also sought to determine whether CRT would enhance repair in steroid-treated pigs, as a model of impaired wound healing.…”
mentioning
confidence: 99%
“…21,22 Although Mr P's caregivers used standard practice guidelines of the time, modern wound care products and knowledge may have limited the scope of his wounds or even allowed healing, if they had been available in the early years of his spinal cord injury. Applying current knowledge of the deleterious effect of acetic acid soaks, for example, may have steered Mr P's health care providers toward other treatment alternatives, 15 such as the use of hydrogels, hydrocolloids, alginates, semipermeable film dressings, wound vacuum pumps, and enzymatic debridement agents. Mr P also may have benefited from the services of multidisciplinary wound care teams that are becoming common in tertiary medical facilities today.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the standard treatment for his wounds during the 1970s (both during hospitalizations and during home care) was acetic acid soaks, a technique that is generally no longer used due to its deleterious effect on granulation tissue. 15 Similarly, Mr P's standing program, because of his hip flexion contractures, may have contributed to his later postural problems. While wearing long leg braces, Mr P stood in parallel bars and was asked to repetitively lean back as far as possible in order to stretch his contracted hip flexor muscles.…”
Section: History Of Decubitus Ulcers and Potential Contributing Factorsmentioning
confidence: 99%
“…Contradictorily, Mayer 124 showed that PVP-I ointment when used in conjunction with the newer gel-type occlusive dressings enhances the healing process. Povidone iodine has been reported to enhance angiogenesis and is a potent microbicidal 125 . A. vera is another important ingredient, which is widely used for its healing, soothing and moisturizing qualities.…”
Section: Current Treatment For Sm Toxicitymentioning
confidence: 99%